PENINGKATAN PENGETAHUAN DAN SIKAP TENTANG CARDIOPULMONARY RESUSCITATION MELALUI PELATIHAN BASIC LIFE SUPPORT PADA PECALANG DAN KADER DI DESA WISATA BONGAN TABANAN - Suindrayasa, I Made; Manangkot, Meril Valentine; Juniartha, I Gusti Ngurah; Antari, Gusti Ayu Ary (Coping: Community of Publishing in Nursing, 2023)
Tourism Village is a program created by a village which aims to attract tourist visits. Bongan is one of the tourist villages in Bali that is currently developing. The tourism industry must be supported by various aspects, especially health. In providing assistance in emergency situations, a person must have good knowledge and a positive attitude. Helping knowledge includes understanding the principles, steps and procedures for helping. A positive attitude in helping is a person's position in wanting to help so that it will be shown by helping behavior. Good preparation, prevention and handling of emergency conditions will provide a sense of security for visiting tourists and tourism service providers in tourist villages. Pecalang and cadres are representatives of the community who can be relied on when emergencies occur. The aim of this study was to determine the effect of Basic Life Support Training on the knowledge and attitudes of pecalang and cadres in handling emergencies, especially regarding cardiopulmonary resuscitation. The method in this research was descriptive analytical method with quasi experimental method with pre-post test. The treatment provided is in the form of Basic Life Support Training in the form of lectures, demonstrations, questions and answers which are carried out face to face. The results of data analysis using the Wilcoxon test showed p-value < 0,05, it means shows an increase in knowledge and attitudes regarding emergency management, especially regarding cardiopulmonary resuscitation through BLS training.